2009
DOI: 10.1007/s12035-009-8056-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effect of Acetyl-l-Carnitine Evidenced by Analysis of Gene Expression in the Rat Brain

Abstract: Acetyl-L-carnitine (ALC), the acetyl ester of L-carnitine, is a naturally occurring substance that when administered at supraphysiological concentrations is neuroprotective. ALC plays an essential role in intermediary and mitochondrial metabolism. It has also neurotrophic and antioxidant actions. ALC has demonstrated efficacy and high tolerability in the treatment of neuropathies of various etiologies, and it is a molecule of considerable interest for its clinical application in various neural disorders, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…We reported before that, in the skeletal muscles of unloaded rats, ALCAR treatment was able to prevent a huge decay of mRNAs level for two kinases AMPK and CaMK2beta able to transduce, respectively, metabolic and neuronal stimuli into PGC-1alpha mitochondrial biogenesis and to increase the mRNAs levels of factors involved in mitochondrial biogenesis cascade. The ability of this molecule to act on gene expression [12,31,75] seems to be supported by the fact that mitochondrial acetylcarnitine provides acetyl groups for nuclear histone acetylation [76]. Furthermore, ALCAR treatment prevented the decrease in old rats of the protein level of factors involved in mitochondrial biogenesis cascade [31,32,77].…”
Section: Resultsmentioning
confidence: 99%
“…We reported before that, in the skeletal muscles of unloaded rats, ALCAR treatment was able to prevent a huge decay of mRNAs level for two kinases AMPK and CaMK2beta able to transduce, respectively, metabolic and neuronal stimuli into PGC-1alpha mitochondrial biogenesis and to increase the mRNAs levels of factors involved in mitochondrial biogenesis cascade. The ability of this molecule to act on gene expression [12,31,75] seems to be supported by the fact that mitochondrial acetylcarnitine provides acetyl groups for nuclear histone acetylation [76]. Furthermore, ALCAR treatment prevented the decrease in old rats of the protein level of factors involved in mitochondrial biogenesis cascade [31,32,77].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, ALC prevents the decay of two kinases of the neuronal (CaMKIIb) and metabolic (AMPK) stimuli axes, localized upstream the PGC1-a signalig pathway. ALC was shown to regulate gene expression in brain and heart (Gadaleta et al 1990;Traina et al 2009). Mitochondrial ALC has been reported to provide acetyl groups for nuclear histone acetylation suggesting this as one of its mechanisms of action (Madiraju et al 2009).…”
Section: Mitochondria-targeted Chemopreventionmentioning
confidence: 99%
“…Besides the afore mentioned role on mitochondrial bioenergetics, which allows brain cells to restore altered redox balance [3,45], ALC is neuroprotective through a variety of other effects such as the increase in PKC activity [41], and modulation of synaptic plasticity via NMDA receptor expression and increase in the production of neurotrophins [202]. Importantly, treatment with ALC induces up-regulation of the gene coding for Hsp72 explaining its protective effects in inflammation, neurodegenerative disorders, and aging [203][204][205]. Another gene identified that is positively modulated by acetylcarnitine in the brain is the mitochondrial voltage-dependent anion channel (VDAC) protein [206].…”
Section: The Carnitine System: Physiological Roles Insufficiency Andmentioning
confidence: 99%